Comparison of grain sorghum and alfalfa for providing heavy metal remediation of sandy soil with different soil amendments and salt stress - Mbarki, Sonia; Talbi, Ons; Skalicky, Milan; Vachova, Pavla; Hejnak, Vaclav; Hnilicka, Frantisek; Al-ashkar, Ibrahim; Abdelly, Chedly; Rahman, Md Atikur; El Sabagh, Ayman; Tlustos, Pavel (Frontiers in Environmental Science, 2022)
Soil salinity and heavy metal (HM) pollution of soil is an ongoing threat to the plants’ survival that adversely affect the crop productivity and global food security. Therefore, an eco-friendly solution is highly desirable for mitigating the adverse affect of toxic pollutants in plants and soils. This study was aimed to explore how municipal solid waste compost (CO) or farmyard manure (M) supplementation regulates biomass yield, mineral nutritions under salinity, and distribution profile of toxic pullutants of (Medicago sativa L.) and sorghum [Sorghum bicolor (L.) Moench]. The CO and M were supplemented with saline (NaCl) soils, the total experiments were conducted for the three consecutive harvestings (H1, H2 and H3) of sorghum and alfalfa. In this study, the CO supplementation highly enhanced biomas yield (dry weight basis in sorghum during H2, while it showed higher in alfalfa during H3., Interestingly, the M significantly increased nitrogen (N2) and potassium (K+) but reduced sodium (Na+) in alfalfa, while the higher Na+ and phosphorus (P) were accumulated in sorghum fertilizer. As a consequence of these finding, a positive correlation was observed among the plant biomass yield, N and K+ content in alfalfa. Conversely, the high Na+ present in soil declined plant biomass in surghum, indicating that CO supplemetaton was not fully effective under high saline soil conditions. However, the N-P-K distribution improved due to CO and/or M supplementation in saline soils, while Cd accumulation was higher in sorghum compared to alfalfa. Therefore, sorghum can be used to clean up contaminated environments. The PCA results showed the same clusters of treatments and amedments were grouped in same plot, which indicated positive correlation beteween the treatment groups and plants, repectively. These results suggest that M supplementation is useful to mitigate saline stress compared to CO in alfalfa, while sorghum can be recommended as to clean up heavy metals (HMs) from soils. This study further suggest a correlation of minerals (N-P-K) boosting and salinity stress reduction in plants. Therefore, organic amendment-based ecofriendly approach can be useful to mitigate salinity stress in plants as well as effective for clean environment and smart agriculture.